2011
DOI: 10.1002/j.1556-6678.2011.tb00072.x
|View full text |Cite
|
Sign up to set email alerts
|

Content Analysis of 32 Years of American Counseling Association Convention Programs

Abstract: A content analysis of American Counseling Association convention sessions offered from 1977 to 2008 was conducted. The intent was to identify changes and trends in the counseling profession. Content of more than 15,000 sessions, including educational programs, keynote presentations, and training sessions, was assigned to 1 of 86 categories. A shift from a career and school focus to clinical and mental health, as well as an increasing emphasis on multicultural; lesbian, gay, bisexual, and transgender; and spiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 14 publications
(7 reference statements)
2
14
0
Order By: Relevance
“…The current study used content analysis, which is an appropriate method when the purpose of a research study is to provide knowledge, offer new insights, make a call for action, and include unobtrusive data sources (Hays & Singh, ; Krippendorff, ). Recent counseling literature that used content analysis raised awareness of specific areas of specialty in the profession (e.g., multicultural counseling; Helwig & Schmidt, ; Singh & Shelton, ; Smith, Ng, Brinson, & Mityagin, ). This study followed steps indicated by Insch, Moore, and Murphy () to conduct a content analysis: (a) identify research questions and texts to be used, (b) specify constructs and keywords to determine units of analysis, (c) generate and purify categories to inform the coding scheme, and (d) assess trustworthiness.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The current study used content analysis, which is an appropriate method when the purpose of a research study is to provide knowledge, offer new insights, make a call for action, and include unobtrusive data sources (Hays & Singh, ; Krippendorff, ). Recent counseling literature that used content analysis raised awareness of specific areas of specialty in the profession (e.g., multicultural counseling; Helwig & Schmidt, ; Singh & Shelton, ; Smith, Ng, Brinson, & Mityagin, ). This study followed steps indicated by Insch, Moore, and Murphy () to conduct a content analysis: (a) identify research questions and texts to be used, (b) specify constructs and keywords to determine units of analysis, (c) generate and purify categories to inform the coding scheme, and (d) assess trustworthiness.…”
Section: Methodsmentioning
confidence: 99%
“…By focusing on specific journals and ACES conferences, we excluded other journals (e.g., Journal for Specialists in Group Work ), conference booklets, and webinars that might include addiction‐related topics. For example, Helwig and Schmidt () found that addictions appeared among the top 20 program titles of ACA conferences during the 1990s. We did not look at these journals, conference booklets, and webinars because the time frame under study was based on the release of the 2009 CACREP Standards.…”
Section: Limitationsmentioning
confidence: 99%
“…It is used in many fields of study—psychology, sociology, education, political science, and others (Fortune, 1981; Neuman, 2003; Smith, 1982). In professional counseling journals, many scholars have used this methodology to analyze and identify themes, trends, submission patterns, and topic areas (Arredondo, Rosen, Rice, Perez, & Tovar‐Gamero, 2005; Bauman et al, 2003; Erford, Miller, Duncan, & Erford, 2010; Erford et al, 2011; Falco, Bauman, Sumnicht, & Engelstad, 2011; Hays & Singh, 2012; Helwig & Schmidt, 2011; Juhnke, Bordeau, & Evanoff, 2005).…”
Section: Methodsmentioning
confidence: 99%
“…There are two forms of content analysis commonly used: word frequency counts and interpretive coding of narrative responses. Word frequency analysis involves the process of reviewing data to determine the frequency of certain keywords, terms, or phrases, whereas interpretative coding involves the process of taking keywords or phrases and assigning them to various categories (Helwig & Schmidt, 2011; Vacc & Loesch, 1993). For this content analysis, both forms used a summative content analysis approach.…”
Section: Methodsmentioning
confidence: 99%
“…The procedures generally include establishing the scope of the investigation, creating sound coding schemes, and generating synthesized, systematic findings (Neuendorf, 2011). Various studies have employed content analysis to examine selected topics in the professional periodicals of psychology and its related fields, such as educational psychology (Pao-Ling, Pin-Haw, Ying-Chun, & Yi-Hua, 2010) and counseling psychology (Helwig & Schmidt, 2011;Falco, Bauman, Sumnicht, & Engelstad, 2011). The focus is typically the treatment of a particular topic or issue, such as the extent of coverage of multiculturalism within training programs in clinical, counseling, and school psychology (Bidell, Ragen, Broach, & Carrillo, 2007) or the nature and extent of quantitative articles in counseling psychology (Nillson, Love, Taylor, & Slusher, 2007), each within one or more selected journals.…”
Section: Content Analysis Of Professional Publicationsmentioning
confidence: 99%